PENDIDIKAN AGAMA KRISTEN DAN TANTANGAN SEKULARISME DI LINGKUNGAN SEKOLAH - Irfan Baso'; Herman Patabang, Filemon Dalef Lamma, Jeniati, Juliani Tandira'pak (CV. ADIBA AISHA AMIRA, 2025)
This study aims to explore the relationship between Christian Religious Education (CRE) and the challenges of secularism in the school environment. In the context of an increasingly pluralistic society influenced by secularism, CRE faces various challenges that threaten the integration of faith values in formal education. Through a literature review, this research analyzes existing literature on the definition of CRE, the impact of secularism on education, and the responses that can be taken to address these challenges. The findings indicate that collaboration among the church, family, and school is key to creating an environment that supports the spiritual development of students. With the right approach, CRE can remain relevant and contribute to the character formation of young generations with a strong faith foundation. This research is expected to provide valuable insights for educators, parents, and church leaders in facing the challenges of secularism in schools.